Peter the Great and the “modernisation” of serfdom in Russia - O. Yu. Yakhshiyan (Вестник университета)
The article examines the transformations of Peter the Great in the context of the evolution of serfdom in Russia. The author substantiates the thesis that during the Peter’s transformations, the so-called “second edition of serfdom” took place, replacing its original, forced by objective conditions of survival and development of the country, estate-legal grounds. The substitution of the serfdom’s grounds is seen primarily in the rejection by the state of the conditionality principle of noble rights to the estate by compulsory lifelong service in the army, namely, this followed from the extension to estates of the patrimony’s possessory format. The analysis of the decree on single inheritance and its interpretations in historiography allowed us to conclude that the liberation of noble land ownership from the encumbrance of compulsory service created a legal basis for the subsequent “freedom of the nobility”, the rapid expansion of the privileges of the “noble estate” and, mainly, the ownership rights to land and peasants. The tax reform of Peter led to the fact that landlords began to assimilate the view of peasants as serfs, completely dependent on them, especially in the conditions of the responsibility imposed by the state on the owner of the estate for the payment of poll taxes and the supply of recruits.